Two new records of Lutzomyia (Diptera: Psychodidae) for the Department of Risaralda, Colombia - BEJARANO, EDUAR ELÍAS; SIERRA, DIANA; VÉLEZ, IVÁN DARÍO (Revista Colombiana de Entomología, 2007)
Two species of Lutzomyia sand flies are recorded for the first time in the department of Risaralda, Colombia: Lutzomyia atroclavata and Lutzomyia sp. series townsendi. The specimens of L. atroclavata were collected with a CDC light trap activated from 18:00 to 06:00 hours, whereas those of Lutzomyia serie townsendi were collected using human baits between 18:00 and 22:00 hours. The main diagnostic morphological characteristics of the species are described.